2015
DOI: 10.3390/ijms16010990
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Supramolecular Nature of Side-Chain Terpyridine-Functionalized Polymer Networks

Abstract: Nowadays, finely controlling the mechanical properties of polymeric materials is possible by incorporating supramolecular motifs into their architecture. In this context, the synthesis of a side-chain terpyridine-functionalized poly(2-(dimethylamino)ethyl methacrylate) is reported via reversible addition-fragmentation chain transfer polymerization. By addition of transition metal ions, concentrated aqueous solutions of this polymer turn into metallo-supramolecular hydrogels whose dynamic mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 91 publications
(116 reference statements)
1
19
0
Order By: Relevance
“…In entangled systems, it has been recently shown that the presence of entanglements does not affect the stickers dynamics, but stickers do affect disentanglement by delaying the relaxation process. 106 In several studies, the strength of the metal–ligand interaction was studied, 119,120 whereas some other research compared the association strength of different types of stickers (based on hydrogen bonding or metal–ligand interaction) (see Figure 8). It was shown that the association strength has a direct influence on the formation of a plateau and delay in the terminal relaxation time.…”
Section: Sticker Positionmentioning
confidence: 99%
“…In entangled systems, it has been recently shown that the presence of entanglements does not affect the stickers dynamics, but stickers do affect disentanglement by delaying the relaxation process. 106 In several studies, the strength of the metal–ligand interaction was studied, 119,120 whereas some other research compared the association strength of different types of stickers (based on hydrogen bonding or metal–ligand interaction) (see Figure 8). It was shown that the association strength has a direct influence on the formation of a plateau and delay in the terminal relaxation time.…”
Section: Sticker Positionmentioning
confidence: 99%
“…[8][9][10] In particular, copolymers containing supramolecular entities as well as cross-linking units have become appealing systems in material science due to their potential to assemble advanced materials with reversible and addressable properties, respectively, such as switchable adhesives and self-healing materials. [11][12][13][14][15][16][17][18] In a solution with multivalent metal ions, the linear polymer chains containing multidentate ligands as the side groups are able to form supramolecular structures. The formation of coordination complexes of multivalent metal ions and the ligands involves the desolvation of both cation and ligand in the solution.…”
mentioning
confidence: 99%
“…We prepare three families of complex: (1) complexes of unmodified polyelectrolytes (pA/pD), (2) complexes of divalent transition metals ions with only a single modified polyelectrolyte (pD 01 -M 2+ ), (3) complexes in which one of the polyelectrolyte partners is modified (pA 01 /pD-M 2+ , pA/pD 01 -M 2+ ), and (4) complexes in which both are terpyridylated (pA 01 /pD 01 -M 2+ ). Non-TC3 complexes of families (1) and (2) know an extensive literature, [20][21][22] whereas (3) and (4) have not been prepared nor studied.…”
Section: Resultsmentioning
confidence: 99%